Islamic Education as an Active Mediator in The Vortex of Post-Truth Polarization - Karim, Abdul Rahim; Margono, Budi Prasetyo; Sugianto, Hendi; Fitriani, Ely; Khoiriyah, Siti (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The world is facing a post-truth era characterized by massive disinformation and the dominance of emotions, which in Indonesia has been accelerated by social media, creating sharp political and social polarization. This condition threatens social cohesion and challenges the relevance of educational institutions. This study aims to formulate and conceptually justify the new role of Islamic education, namely shifting from a passive-preventive "moral fortress" to a proactive-mediative "active mediator" in facing the vortex of polarization. This study also aims to outline a relevant pedagogical framework and analyze the implementation challenges and long-term implications of this repositioning of roles. This study uses a qualitative approach with a systematic review method. Data were collected from various academic sources such as journals, books, and reports relevant to the post-truth era, polarization, and Islamic Religious Education (IRE). Data analysis was conducted thematically, synthetically, and interpretively to construct conceptual arguments. The results show that the conventional IRE model is no longer adequate to equip students who are vulnerable to disinformation. A repositioning of the role as an "active mediator" is needed, which includes three dimensions, namely self-mediation (intrapersonal), interpersonal-mediation (interpersonal), and public-mediation (proactive). To achieve this, pedagogical strategies must integrate critical digital literacy, problem-solving, and innovative learning models such as project-based learning. The advantage of IRE is its ability to frame these skills within Islamic ethical values, such as tabayyun (clarification) as a conscious resistance to divisive social media algorithms. Although its implementation faces major challenges, particularly in terms of teacher competence and institutional resistance, this transformation of roles is highly significant. Its success promises to strengthen social cohesion and build national digital resilience, as well as contribute to the health of digital democracy in Indonesia